LGBTQ+ Aging Research in Canada: A 30-Year Scoping Review of the Literature - Wilson, Kimberley (Geriatrics (Basel), 2021)
Canada has a unique socio-political history concerning the inclusion of lesbian, gay, bisexual, transgender, and queer (LGBTQ+) people. With aging populations, understanding diverse groups of older adults is paramount. We completed a systematic search and scoping review of research in Canada to quantify and articulate the scale and scope of research on LGBTQ+ aging. Our search identified over 4000 results and, after screening for relevance, our review focused on 70 articles. Five major themes in the literature on LGBTQ+ aging in Canada were identified: (1) risk, (2) HIV, (3) stigma, and discrimination as barriers to care, (4) navigating care and identity, (5) documenting the history and changing policy landscapes. Most of the articles were not focused on the aging, yet the findings are relevant when considering the lived experiences of current older adults within LGBTQ+ communities. Advancing the evidence on LGBTQ+ aging involves improving the quality of life and aging experiences for LGBTQ+ older adults through research.